One-dimensional analysis of the behaviour of wet steam at different inlet conditions - Malek N.A.; Hasini H.; Yusoff M.Z. (2023)
The main aim of this paper is to estimate the likely behaviour of steam during an expansion process with the variation in the total inlet temperature. It is well-acknowledged that the position of limiting supersaturation was dependent on the steam conditions at inlet. Based on this hypothesis, an improved mathematical model is developed to observe the effect of changing the inlet total temperature to the flow properties. In the present work, a one-dimensional (1-D) time-marching compressible Euler solver that uses the second order cell-vertex finite volume spatial discretization and fourth orders Runge-Kutta temporal integration has been developed. Artificial viscosity is added by using Jameson's type 2nd and 4th. A single dimension is considered here as to demonstrate the main effects of spontaneous condensation without necessary complexity. The boundary conditions across the nozzle are imposed in the calculations. Based on the calculation, it is clear that the Mach number and pressure ratio is a good representation to the onset of condensation and are highly dependent on the total inlet temperature. 2012 American Institute of Physics.